Systems of care literature review - Colorado Institute of Public Policy, author; Jefferson County (Colo.). Division of Human Services, author (Colorado State University. Libraries, 2004)
Systems of Care (SOC) was developed for the delivery of children's mental health services (Stroul and Friedman, 1996). Given the complexity of services needed, the number of agencies involved in the child's life as well as the disarray of mental health service delivery in general (Grady, 2003), SOC provides a coherent framework upon which to better meet the needs of the child and family. The child and family focus and an emphasis on providing services that are comprehensive, coordinated, community-based, culturally competent and individualized (Stroul, 1996) are SOC principles that fit well with serving the needs of children in the welfare system.
Connecting Communities to Kids, Jefferson County Division of Human Services Systems of Care Project.
Not digitized by CSUL Digital Services.
Keywords: Community-based child welfare -- Colorado -- Jefferson County; Community-based family services -- Colorado -- Jefferson County; Community-based social services -- Colorado -- Jefferson County